Managing the self : a critical analysis of bullet journaling content on YouTube - Nieto, Julia Martinez (2021)
This study analysed the practice of bullet journaling through its portrayal in instructional YouTube videos. Applying a multimodal critical discourse analysis methodology, the study examined the main characteristics of bullet journaling in terms of its main features and functions, and related said characteristics to the underlying discourses framing the practice. The data set consisted of ten videos on bullet journaling from AmandaRachLee’s YouTube channel. The multimodal analysis focused on the journal as a visual canvas as well as on the contents of the videos’ voice-overs, where the creator talked about her thoughts on bullet journaling and her journaling process. The study found that the journal’s aesthetic dimension, as well as bullet journaling’s portrayal as a pleasant activity which allows users to connect to positive emotions, were foregrounded in the videos. The journal’s role as a tool for mediating emotion emerged as a central aspect of the practice, which also mediated the practitioner’s relationship with the self-work that was performed through the journal. This approach to self- and productivity work resonated with neoliberal discourses on individual responsibility, the nature of emotion, and expectations related to emotional management and the upkeep of a “functional self” in a neoliberal context.